Implementasi Pendidikan Berkelanjutan Sebagai Upaya Peningkatan Pendidikan Berkualitas di Sekolah Dasar - Damayanti, Ayen Vera; Nugraheni, Nursiwi (Yayasan Daarul Huda Kruengmane, 2024)
This article discusses the implementation of SDGs in order to improve quality education. SDGs have 17 goals which are very good goals to advance a country. Education is the most basic foundation, because with education the goal of achieving SDGs can be achieved. Elementary schools play an important role in instilling moral values and character in students. The research was conducted at SDN Wonodri from January to March 2024. The method used is descriptive qualitative which concludes the results of a series of continuing education-based activities carried out at SDN Wonodri. From a series of activities carried out can foster intelligence, creativity, skills, confidence, environmental care attitudes, and body health for students in accordance with the goals of achieving SDGs.